DANCE, RHYTHM AND BODY: MEANINGS AND REPRESENTATIONS IN CANDOMBLÉ (Fiep Bulletin - online, 2017)
This article deals with form in a circle as the African position themselves to dance, and that this legacy is manifested in Candomblé in Brazil in the concluding moments of his beliefs to the Orishas, seek to highlight the representation and symbolism of dance, rhythm and body in religious moments in the holy yards. Describe the dance associated with the orishas and their stories through gestural, these acts born of a peculiar symbology to a religious space that carries in its African heritage representations. In this context, we discuss that religious moments of Candomblé dances are organized into choreography is during the celebration or the incorporation of-saint children-, and that they are distinct, and only a long coexistence as ritual, those who attend consent know them and describes them, that is, what the orisha being represented. However, the corner will also address historical issues and stages experienced by orishas on the earth plane and touches performed on percussion instruments will give the style tone to be danced at the time that the orishas present in candomblé yard. Moreover, we evidenced the body's relationship to religion in an intense and extensive learning process, which are internalized according to the dogmas, religious foundations and the archetype of the orishas, bequests that are transmitted to the initiated in Candomblé by older religious of community.
Keywords: Candomblé; Dance; Body